"I Was Not Told That I Still Have The Virus": Perceptions of Utilization of Option B+ Services at a Health Center in Malawi. (31st August 2019) - Mulewa, Patience; Satumba, Egrina; Mubisi, Christopher; Kandiado, Joseph; Malenga, Tumaini; Nyondo-Mipando, Alinane Linda
Utilization of the prevention of mother-to-child transmission of HIV (PMTCT) services remains a challenge as losses to follow-up are substantial. This study explored factors that influence adherence to maternal antiretroviral (ARV) medications among PMTCT mothers in Malawi. We conducted a descriptive qualitative study from September 2016 to May 2017 using purposive sampling among 16 PMTCT mothers and 4 key informant interviews with health-care workers. Data were audio-recorded and analyzed thematically. The factors that influence adherence to maternal ARV medications include the quality of PMTCT services and social support. Factors that impede adherence include suboptimal counseling women receive on ARV medications, cost of travel, and conflicting advice from religious institutions. Adherence to maternal ARV medications will require the use of existing social support systems in a woman's life as a platform for delivery of the drugs while also maintaining continued and comprehensive counseling on the benefits of maternal ARV medications.